Inhibition of transforming growth factor-β via the activin receptor-like kinase-5 inhibitor attenuates pulmonary fibrosis - Koh, Rhun Yian; Lim, Chooi Ling; Uhal, Bruce David; Abdullah, Maha; Vidyadaran, Sharmili; Ho, Coy Choke; Seow, Heng Fong (Spandidos Publications, 2015)
Idiopathic pulmonary fibrosis is a chronic pulmonary disease that is characterized by formation of scar tissue in lungs. Transforming growth factor-β (TGF-β) is considered an important cytokine in the pathogenesis of this disease. Hence, the antifibrotic effect of an inhibitor of the TGF-β type I receptor, namely, SB 431542, was investigated in our study. SB 431542 was used to treat TGF-β-treated IMR-90 cells; the expression of α-smooth muscle actin (α-SMA) was detected at the protein level by using an anti-α-SMA antibody, and at the gene level by reverse transcription-quantitative PCR. The effect of the inhibitor on cell proliferation was determined by a cell growth assay. The inhibitor was also administered into bleomycin-treated mice. Histopathological assessment and determination of total collagen levels were carried out to evaluate the severity of lung fibrosis in these mice. Our results demonstrated that treatment with SB 431542 inhibits TGF-β‑induced α-SMA expression in lung fibroblasts, at both the protein and the mRNA levels (P<0.05). However, the inhibitor did not significantly reduce lung fibroblast proliferation. In the bleomycin-induced pulmonary fibrosis mouse model, bleomycin treatment caused important morphological changes, accompanied by an increase in the collagen level of the lungs. Early treatment with SB 431542 prevented the manifestation of histopathological alterations, whereas delayed treatment significantly decreased the collagen level (P<0.05). These results suggest that inhibition of TGF-β signaling, via inhibition of the activin receptor-like kinase-5 (ALK-5) by SB 431542, may attenuate pulmonary fibrosis.